Karakteristik Snack Ekstrusi dengan Penambahan Grit Ikan Gabus (Channa striata) - Nuraenah, Nani; Deviarni, Ika Meidy; Fitriyani, Evi (Journal Galung Tropika, 2022)
Snack food is one type of product produced by extrusion technology. Generally, extruded snack products are high in carbohydrates and low in protein because the main ingredients used are ingredients with high starch content, such as corn and rice. The protein content of extruded snack products can be increased by adding high-protein ingredients such as snakehead fish. The addition of snakehead fish to snack products can affect the physical and chemical characteristics of the resulting snack. The research aimed to study the effect of the size and concentration of fish grit on the physical characteristics (hardness, fracturability, color, expansion ratio), chemical (moisture content), and hedonic of the extruded snack product with the addition of snakehead fish grit. The study used a factorial completely randomized design consisting of 2 factors, namely factor A (fish grit size) in 3 levels (10, 12, and 20 mesh) and factor B (fish grit percentage) in 2 levels, namely (10%, and 15%). ). As a comparison (control) snacks were used without the addition of fish grit. All treatments were carried out 2 times. The size and concentration of fish grit did not affect the physical characteristics of the extruded snack, either hardness, fracture, or expansion ratio, except that the color of the extruded snack was influenced by the size of the fish grit but not influenced by the concentration or interaction between the size and concentration of the fish grit. The results of the sensory analysis showed that the combination of size and concentration of fish grit did not affect the panelists' acceptance of the sensory parameters of appearance, color, aroma, and texture but did affect the taste parameters.